2019
DOI: 10.1021/acsnano.9b06484
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Wrapped CuV2O6 Nanobelts as High-Capacity and Long-Life Cathode Materials of Aqueous Zinc-Ion Batteries

Abstract: Rechargeable aqueous zinc-ion batteries are considered as a promising alternative of lithium-ion batteries for stationary energy storage because of their economical and high safety quality. However, their widespread application is still impeded by the development of cathode materials with poor energy density and limited long-term stability. Herein, we report a high-performance CuV 2 O 6 cathode material for aqueous zinc-ion batteries and elucidate the zinc-storage mechanism. The reversible phase transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
177
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(184 citation statements)
references
References 43 publications
6
177
0
1
Order By: Relevance
“…[ 2–7 ] Among them, aqueous zinc batteries have aroused extensive interest and attention, which benefits from many advantages of zinc anode, including high theoretical capacity (820 mAh g −1 ), appropriate redox potential (−0.762 V vs the standard hydrogen electrode (SHE)), and intrinsic safety in aqueous system. [ 8–20 ] Inspired by conventional Li + storage reaction, intercalation reaction of transition metal oxides are employed to storage Zn 2+ in the mild aqueous solution. For example, Zn 0.25 V 2 O 5 · n H 2 O, [ 9 ] Prussian blue analogue, [ 15 ] VO 2 , [ 17 ] MnO 2 , [ 18 ] Zn 3 V 2 O 7 (OH) 2 ·2H 2 O, [ 19 ] CuV 2 O 6 [ 20 ] have been used as cathodes for zinc batteries.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 2–7 ] Among them, aqueous zinc batteries have aroused extensive interest and attention, which benefits from many advantages of zinc anode, including high theoretical capacity (820 mAh g −1 ), appropriate redox potential (−0.762 V vs the standard hydrogen electrode (SHE)), and intrinsic safety in aqueous system. [ 8–20 ] Inspired by conventional Li + storage reaction, intercalation reaction of transition metal oxides are employed to storage Zn 2+ in the mild aqueous solution. For example, Zn 0.25 V 2 O 5 · n H 2 O, [ 9 ] Prussian blue analogue, [ 15 ] VO 2 , [ 17 ] MnO 2 , [ 18 ] Zn 3 V 2 O 7 (OH) 2 ·2H 2 O, [ 19 ] CuV 2 O 6 [ 20 ] have been used as cathodes for zinc batteries.…”
Section: Figurementioning
confidence: 99%
“…[ 8–20 ] Inspired by conventional Li + storage reaction, intercalation reaction of transition metal oxides are employed to storage Zn 2+ in the mild aqueous solution. For example, Zn 0.25 V 2 O 5 · n H 2 O, [ 9 ] Prussian blue analogue, [ 15 ] VO 2 , [ 17 ] MnO 2 , [ 18 ] Zn 3 V 2 O 7 (OH) 2 ·2H 2 O, [ 19 ] CuV 2 O 6 [ 20 ] have been used as cathodes for zinc batteries. However, the hydrated Zn 2+ and H + usually result in large volumetric change and serious structural collapse of these inorganic compounds with the insertion of a large amount of hydrated Zn 2+ , [ 21–25 ] showing significant capacity fading and limited cycle life.…”
Section: Figurementioning
confidence: 99%
“…More importantly, it is obvious that the excessive transition metal ions could precipitate and reduce to the high conductivity metal particles (such as Cu, Ag, etc.) during the process of discharge (Figure 2d) [12,50,51] . Although such effect of the conductive network constructed by this method is more significant and lasting, the intrinsic structure collapse of the electrode caused by cation precipitation is partially irreversible, ultimately reducing the comprehensive electrochemical performances.…”
Section: The Role Of Interlayer Doping In Layered Vanadium Oxidesmentioning
confidence: 99%
“…On the other hand, the unique electronic characteristics endow them with considerable pseudocapacitance behaviour especially in aqueous systems (such as more than 400 mAh g −1 of V 6 O 13 in AZIBs) [7] . Furthermore, most vanadium‐based oxides, including the VO 2 , [8,9] V 2 O 5 , [10] V 3 O 7 , [11] MV 2 O 6 , [12] M 3 V 2 O 8 , [13] etc. with layered structure, could allow interlayered 2D diffusion owing to the open framework [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable zinc batteries using mild aqueous electrolytes are attracting extensive attention owing to the low cost, nontoxicity,high safety,high capacity,and low potential of the Zn anode. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Recently,v arious cathode materials,s uch as MnO 2 , [18][19][20][21][22][23] vanadium oxides, [24][25][26][27][28][29][30][31][32][33] and hexacyanoferrate, [34][35][36][37] have been coupled with aZ na node to build aqueous Zn batteries,w hich show promising electrochemical performance.U nfortunately,t he achieved performances are still far from those required for practical applications.Ithas been demonstrated that the cathodic reaction in arechargeable Zn battery is based on reversible Zn 2+ and/or H + insertion in the host materials (i.e., MnO 2 ,V O 5 ,o rhexacyanoferrate). However,t he insertion/extraction of the hydrated Zn 2+ (i.e., [Zn(H 2 O) 6 ] 2+ )a nd H + (i.e., H 3 O + )g enerally leads to the structure collapse of host materials in the cathode, [12,13,18] which greatly limits the cyclelife of rechargeable Zn batteries.…”
Section: Introductionmentioning
confidence: 99%